Multidisciplinary problem-based industrial engineering project - Kuptasthien, Natha (2007)
The new paradigm for engineering education nowadays expects new engineering graduates from universities to have more qualifications in both technical and enterprising skills. This paper objective is to discuss a success story of setting multi-disciplinary project groups to solve problems occurred in a case study of an industrial company. The final year of an industrial engineering undergraduate program at Rajamangala University of Technology Thunyaburi requires a 3-credit in Industrial Engineering Project. A student team has a year to search for topic, conduct the study and make final conclusion. The cooperative partner is a well-known Thai herbal company. The project methodology included a visit to the company and discussion with the executives, defining problems and study scopes using various techniques, setting up a project team, gathering data, analyzing data, suggesting action plans to solve problems, implementing the proposed plan, evaluating results and making a final conclusion. The project team integrated multidisciplinary areas of marketing, financing and industrial engineering. The results showed magnificent outcomes in marketing, financing and production. Marketing department had a successful re-branding launch. The shareholders agreed to invest more money to strengthen the financial status. Moreover, there were some productivity improvements from production department.